Global economic cost of smoking-attributable diseases - Goodchild, Mark; Nargis, Nigar; Tursan d'Espaignet, Edouard (Tobacco control, 2018)
BackgroundThe detrimental impact of smoking on health has been widely documented since the 1960s. Numerous studies have also quantified the economic cost that smoking imposes on society. However, these studies have mostly been in high income countries, with limited documentation from developing countries. The aim of this paper is to measure the economic cost of smoking-attributable diseases in countries throughout the world, including in low- and middle-income settings.MethodsThe Cost of Illness approach is used to estimate the economic cost of smoking attributable-diseases in 2012. Under this approach, economic costs are defined as either ‘direct costs' such as hospital fees or ‘indirect costs’ representing the productivity loss from morbidity and mortality. The same method was applied to 152 countries, which had all the necessary data, representing 97% of the world's smokers.FindingsThe amount of healthcare expenditure due to smoking-attributable diseases totalled purchasing power parity (PPP) $467 billion (US$422 billion) in 2012, or 5.7% of global health expenditure. The total economic cost of smoking (from health expenditures and productivity losses together) totalled PPP $1852 billion (US$1436 billion) in 2012, equivalent in magnitude to 1.8% of the world's annual gross domestic product (GDP). Almost 40% of this cost occurred in developing countries, highlighting the substantial burden these countries suffer.ConclusionsSmoking imposes a heavy economic burden throughout the world, particularly in Europe and North America, where the tobacco epidemic is most advanced. These findings highlight the urgent need for countries to implement stronger tobacco control measures to address these costs.